Pedagogy of narration - Leonardo Acone (Ricerche di Pedagogia e Didattica)
This essay aims to emphasize the importance of investigating the pedagogical dimension of literature, reading, writing, images, and other narrative arts within the framework of a possible pedagogy of narration. This field of study is growing, with the emergence of new teachings, new research paths, and the establishment of new academic positions within Italian universities. For there to be a “pedagogy of narration”, it is essential that the analysis of what is narrated, read, heard, or observed focuses on the educational essence that emanates from narratives. This is not about answering the simple question of what a particular text can or cannot teach, but rather about identifying a successful formula that combines artistic/literary value, historical/testimonial significance, and educational persistence with scientific and epistemological coherence. This would allow the connection between the pedagogy of history, the pedagogy of memory, and, more broadly, the pedagogy of narration.